(3GdYdb GdKejf hGdLhgQ GdfajS GdeNdU ef YjhH GdRja hGdZT hGdJOdjSs - (3SjOj Hf GdeNJGQ Hf GdgjH GdGHjQj,J (B1283 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efRd GdQMeI heajV GdfYeI HYO GdbfhW hGTJOGO GdCReI gPG , hdjcf ai cQje Ydec hSdje Phbc hagec CjgG GdCN GdQTjO Cf GdJbhi gi QCS cd hLeGY cd NjQ hfYeI , hCfgG cjejGA hGdSYGOI s
(3BNQgG (B:s
(3hGYde Cf GdahGFO ai GdYbGFO hedGc GdNhGU UOb GdENdGU hYdjc HGdeMGaXI Ydi ChQGOc aEfgG Yjf EeOGOc GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3cJHgG fGSNgG ddUGOb Hf eMeO Hf eQGHW ecI s
(3MhGagG eJbUaI GdChQGb s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs